Problems of formation of terminological system in hindi language - Кокеевa Д. М.; Бокулевa Б. С.; Турaр A. C. (Journal of Oriental Studies, 2018)
A consistent and systematic study of changes in the development and formation of banking terms due to the need of time. Whereas the scope of banking terms is established, as in other industries, and the process of development is going on. This article investigated aspects of the emergence and establishment of definitions of the banking terminology.